COMPARATIVE ANALYSIS OF POLITICAL PARTIES’ DRAFTS ON THE CONSTITUTION OF MONGOLIA - Ч.Өлзийсайхан; Д.Ундрах; Ц.Батболд (Politology, 2023)
Within the framework of this research, we have set an objective to display a short summary of the analysis on Mongolian parliament, a brief introduction of political parties’ versions of governance in constitution, and tendencies of public opinions as well as explaining the advantages and disadvantages of parliamentary and presidential systems.